The relationship between college students’ legal cognition and maladaptive risk-taking behaviors: the moderating effect of need for cognitive closure - Hu, Yu; Ding, Qiang; Liu, Hui; Xu, Shuhui (Frontiers in Psychology, 2025)
Legal socialization refers to the developmental process through which individuals form beliefs, values, and attitudes toward the law. A key component of this process is legal cognition, which includes concrete legal cognition and abstract legal cognition. While prior research links legal cognition to reduced antisocial behavior, its role in maladaptive risk-taking remains unclear. Additionally, how the two dimensions of Need for Cognitive Closure (NFC)—need for structure and decisiveness—moderate these effects is not well understood. In this study, 396 college students completed measures of legal cognition, maladaptive risk-taking, and NFC. Results showed that both concrete and abstract legal cognition negatively predicted maladaptive risk-taking. Need for structure strengthened these negative associations, while decisiveness weakened the link between concrete legal cognition and risk-taking but had no significant effect on abstract legal cognition. These findings suggest that the two types of legal cognition play distinct protective roles, and that the two dimensions of NFC differently shape how legal beliefs influence risk-taking behavior, providing guidance for teachers and school administrators in designing interventions to reduce maladaptive risk-taking among students.